Development of argument-driven inquiry model with blended learning approach in environmental science course - Rizqa Devi Anazifa; P. Paidi; Anggi Tias Pratama; Atik Kurniawati (Research and Development in Education (RaDEn), 2024)
In response to the rapidly evolving world, students should be equipped with the thinking skills such as argument skills. This skill should be promoted using designed model of teaching which give students opportunities to develop and present arguments particularly in science program. In addition, as we navigate the complexity of a digital age, learning process should align with the demands of the digitally driven learning activities. Recognizing the need for the innovative pedagogical strategies, this research aims to design the novel teaching model called argument-driven inquiry based blended learning in environmental science course for undergraduate students. The study was research and development which included three phases analyze, design, and develop for the teaching model development and its validation. This research incorporated argument-driven inquiry with blended learning approach which produced eight phases of learning activities, 1) identify task and guiding question, 2) design method and data collection, 3) develop an initial argument, and 4) argumentation session which conducted offline, followed by 5) discussion, 6) investigation report writing, 7) report peer-review, 8) revise and submit the report which conducted online. This model validation involved four experts in biology learning strategies. The validation includes the validation of the model development as well as its learning instruction such as lesson plan and students’ worksheet. The results of model validation showed that the argument-driven inquiry model with blended learning approach was valid and can be implemented in the environmental course.